2021
DOI: 10.1186/s40104-020-00543-1
|View full text |Cite
|
Sign up to set email alerts
|

Rumen microbiome structure and metabolites activity in dairy cows with clinical and subclinical mastitis

Abstract: Background Due to the high prevalence and complex etiology, bovine mastitis (BM) is one of the most important diseases to compromise dairy cow health and milk quality. The shift in milk compositions has been widely investigated during mastitis, but recent studies suggested that gastrointestinal microorganism also has a crucial effect on the inflammation of other peripheral tissues and organs, including the mammary gland. However, research focused on the variation of rumen inner-environment duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 56 publications
(37 reference statements)
5
48
0
Order By: Relevance
“…A study on rumen microbes with cow mastitis revealed that the infected degree of udder. The concentrations of lactic acid, acetate, propionate, butyrate, valerate, and total volatile fatty acids in rumen were significantly decreased (63). Bacteria associated with intestinal inflammation and oral inflammation are significantly increased in the rumen of dairy cows with clinical mastitis.…”
Section: Rumen Microbiome Metabonomics Analysis Of Cow Mastitismentioning
confidence: 90%
See 2 more Smart Citations
“…A study on rumen microbes with cow mastitis revealed that the infected degree of udder. The concentrations of lactic acid, acetate, propionate, butyrate, valerate, and total volatile fatty acids in rumen were significantly decreased (63). Bacteria associated with intestinal inflammation and oral inflammation are significantly increased in the rumen of dairy cows with clinical mastitis.…”
Section: Rumen Microbiome Metabonomics Analysis Of Cow Mastitismentioning
confidence: 90%
“…Bacteria associated with intestinal inflammation and oral inflammation are significantly increased in the rumen of dairy cows with clinical mastitis. The ruminiclostridium_9 and enterorhabdus were increased with the increasing of methenamine, 5-hydroxymethyl-2-furancarboxaldehyde (5-HMF) and 6-methoxymellein in the rumen of subclinical mastitis (63). In addition, the bacteria and probiotics produced by shortchain fatty acids (SCFAs) in rumen were significantly reduced with decreasing of 2-phenylbutyric acid (2-PBA) (63).…”
Section: Rumen Microbiome Metabonomics Analysis Of Cow Mastitismentioning
confidence: 99%
See 1 more Smart Citation
“…As our study design was intended to be a proof-of-principle concerning a species-level detection of potentially pathogenic bacteria in milk, we assessed whether we could find such species in our dataset. However, these bacteria could also be simple contaminants, as previously reported [12,14,[46][47][48][49]. Nevertheless, in many of those previously performed studies, short-amplicon sequencing strategies were applied targeting either V1-V2, V3-V4 or V4 alone.…”
Section: Using Full-length Sequencing Approaches For Microbial Monitoringmentioning
confidence: 99%
“…The contamination of milk with bacteria mainly results from poorly cleaned and poorly disinfected milking equipment, lack of hygiene during milking or handling of the milk, and bacteria present in the barn. Moreover, the presence of environmental pathogens such as Escherichia coli , Klebsiella spp., Streptococcus dysgalactiae and Streptococcus uberis may contribute to the development of mastitis in dairy cattle, which is an “occupational disease” of high-yielding dairy cows [ 5 , 6 ]. The disease is caused by bacteria and other microorganisms that enter the teats.…”
Section: Introductionmentioning
confidence: 99%